High variability of individual longitudinal motor performance over five years in very preterm infants. (December 2016) - Janssen, Anjo J.W.M.; Oostendorp, Rob A.B.; Akkermans, Reinier P.; Steiner, Katerina; Kollée, Louis A.A.; Nijhuis-van der Sanden, Maria W.G.
Highlights: Motor performance improved over 5 years by almost 1 standard deviation. At 5 years, girls perform better for manual dexterity and balance. VPT infants showed high individual variability in longitudinal motor performance. Variability of individual results hampers evaluation of motor interventions in clinical care and research. Future research should focus on norm referenced motor test based on longitudinal data. Abstract: Aim: To determine longitudinal motor performance in very preterm (VPT) infants from 6 months to 5 years of age for the entire cohort of infants, according to gender and gestational age and at the individual level. Method: Single-center, prospective longitudinal study of 201 VPT infants (106 boys) without severe impairments. Outcomes: Motor performance was assessed with the Bayley Scales of Infant Development (BSID-II-MS: 6, 12, 24 months) and the Movement Assessment Battery for Children (MABC-2-NL: 5 years). Results: At 6, 12, and 24 months and then at 5 years, 77%, 80%, 48%, and 22% of the infants, respectively, showed delayed motor performance (<−1SD). At 5 years, girls performed significantly better than boys in manual dexterity and balance. Mixed model analyses: that examined interactions between time and gender and time and gestational age, revealed no significant interactions. The variance at child level was 29%. Linear mixed model analysis revealed that mean z-scores of −1.46 at 6 months of age declined significantly to −0.52 at 5 years. Individual longitudinal motor performance showed high variability. Implications: Longitudinal motor performance improved almost 1 SD over five years. However, the variability of individual longitudinal motor performance hampers evaluation in clinical care and research.